2021
DOI: 10.1021/acs.jpclett.1c03427
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Exciton and Carrier Relaxation Dynamics of Two-Dimensional (2D) and Quasi-2D Tin Perovskites

Abstract: The dynamics of exciton and free-carrier relaxation of low-dimensional tin iodide perovskites, BA2FA n–1Sn n I3n+1, where n = 1 (N1), 2 (N2), 5 (N5), and 10 (N10), were investigated with femtosecond transient absorption spectra (TAS). The absorption and photoluminescence spectra of N1 and N2 show exciton characteristics due to quantum confinement, whereas N5 and N10 display a free-carrier nature, the same as for bulk three-dimensional (3D) films. The TAS profiles were fitted according to a global kinetic model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…Tin perovskite solar cells (TPSCs) have become some of the most promising candidates for lead-free perovskite solar cells as a next-generation photovoltaic technology. However, the intrinsic problems of TPSCs, such as Sn 2+ /Sn 4+ oxidation, rapid crystallization, poor stability, and so on, need to be solved to promote the device performance for TPSCs. Many approached have been reported to tackle these problems; among them, additive engineering is a promising approach to passivate the surface defects, reduce Sn 4+ back to Sn 2+ , modulate crystallization, form a surface-protected low-dimensional perovskite, and so forth. Tin fluoride (SnF 2 ) and ethylene diammonium diiodide (EDAI 2 ) are two of the most common additives to prevent Sn 2+ /Sn 4+ oxidation as well as to regulate the crystallization for TPSC. , In addition to these two additives, others such as cationic, anionic, and multifunctional additives have been widely considered for TPSCs. ,, We have previously reported organic cations such as guanidinium (GA), 2-hydroxyethylammonium (HEA), and aziridinium (AZ) as A-site cations to cocrystallize with formamidinium (FA) to form cocationic tin perovskites for enhanced performance and stability for TPSCs. In the present study, a new organic cation, imidazolium (IM), was implemented to mix with FA to form a cocationic tin perovskite.…”
mentioning
confidence: 99%
“…Tin perovskite solar cells (TPSCs) have become some of the most promising candidates for lead-free perovskite solar cells as a next-generation photovoltaic technology. However, the intrinsic problems of TPSCs, such as Sn 2+ /Sn 4+ oxidation, rapid crystallization, poor stability, and so on, need to be solved to promote the device performance for TPSCs. Many approached have been reported to tackle these problems; among them, additive engineering is a promising approach to passivate the surface defects, reduce Sn 4+ back to Sn 2+ , modulate crystallization, form a surface-protected low-dimensional perovskite, and so forth. Tin fluoride (SnF 2 ) and ethylene diammonium diiodide (EDAI 2 ) are two of the most common additives to prevent Sn 2+ /Sn 4+ oxidation as well as to regulate the crystallization for TPSC. , In addition to these two additives, others such as cationic, anionic, and multifunctional additives have been widely considered for TPSCs. ,, We have previously reported organic cations such as guanidinium (GA), 2-hydroxyethylammonium (HEA), and aziridinium (AZ) as A-site cations to cocrystallize with formamidinium (FA) to form cocationic tin perovskites for enhanced performance and stability for TPSCs. In the present study, a new organic cation, imidazolium (IM), was implemented to mix with FA to form a cocationic tin perovskite.…”
mentioning
confidence: 99%
“…In addition, both Tp-PSK and Py-PSK displayed high PLQYs of 68.3 ± 3% and 61 ± 5% with average PL lifetimes of 3.7 and 4.2 ns; the short lifetime in nanosheets was also indicative of the strong confinement effect (Figure S5). This n = 3 layered structure was also proven by XRD analyses (Figure D); both nanosheets possessed periodic LD diffraction peaks at low-angle reflections (<14°) in layered perovskite crystals. , Coupled with XRD results, the Williamson–Hall method (W–H) was used to analyze the crystal lattice strain in Tp/Py-PSK (Figure S6). A significant lattice compressive strain (ε) was observed in Tp-PSK which was likely induced by the stronger lattice distortion; the simulated distorted crystallographic structure is depicted in Figure S7.…”
mentioning
confidence: 73%
“…[33,34] Compared to 3D perovskites, 2D perovskites showed strong spin-orbit coupling and giant Rashba splitting. [35] By femtosecond transient absorption spectra (TAS) strategy, Diau et al proved that the (BA) 2 FASnI 4 and (BA) 2 FASn 2 I 7 perovskites showed excitonic behavior, whereas the (BA) 2 FA 4 Sn 5 I 16 and (BA) 2 FA 9 Sn 10 I 31 perovskites generated free carriers upon excitation. [36] Only (BA) 2 FASnI 4 compounds observed asymmetric excitonic band anchoring at 630 nm.…”
Section: Excitonic and Carrier Behaviormentioning
confidence: 99%